ON THE NATURE OF BACTEREMIA IN EXPERIMENTAL PNEUMOCOCCAL PNEUMONIA IN THE DOG : I. RELATIONSHIP OF NATURAL PNEUMOCOCCIDAL-PROMOTING ACTIVITY OF THE SERUM TO BLOOD INVASION - Robertson, O. H. (The Rockefeller University Press, 1953)
In a study of the relationship of natural antipneumococcal immune substances to the incidence and course of bacteremia in dogs with experimental pneumococcus pneumonia the following findings came to light: (1) In non-bacteremic animals, natural immune substances, as measured by the pneumococcidal-promoting action of the serum, continue to be present in relatively undiminished concentration throughout the course of the infection. (2) With the advent of bacteremia these immune properties of the blood tend to decrease or disappear, depending on the degree of bacteremia and the length of the disease course, but in certain instances they persist despite the presence of large numbers of circulating pneumococci. (3) Disappearance of natural immune substances from the blood during bacteremia is followed by their reappearance upon cessation of the bacteremia. (4) Bacteremic blood containing antipneumococcal immune substances and a sufficient quantity of leucocytes is capable of destroying in vitro relatively large numbers of pneumococci and will often sterilize itself. (5) The sequence of bacteremia first, then diminution and disappearance of humoral immunity excludes this antipneumococcal action of the blood as being the principal inhibitor of blood invasion. These observations have been interpreted as indicating that the bacteremic state consists of a constant escape of pneumococci from the pulmonary lesion and an attempt on the part of the body to compensate for the depletion of circulating immune substances resulting from their progressive immobilization by the pneumococci and their products. Thus, the loss or retention of humoral immune substances in the presence of bacteremia would appear to depend on the rate at which the body can provide new supplies of antibodies and on the number of pneumococci being discharged into the circulation. While the pneumococcidal action of the blood may not be sufficient to prevent the occurrence of bacteremia our study provides ample evidence that it exerts a potent restraining effect on the increase in numbers of pneumococci in the circulation.